2019
DOI: 10.3389/fimmu.2019.00820
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T-Cells With High Common γ Chain Expression and Disturbed Cytokine Production Are Enriched in Children With Type-1 Diabetes

Abstract: The common gamma chain (γ c ) contributes to the formation of different cytokine receptors [e.g., IL-2 receptor (IL-2R), IL-7R, and IL-15R], which are important for generation of self-reactive T-cells in autoimmune diseases, like in type 1 diabetes (T1D). Whereas, the roles of membrane and soluble IL-2Rα and IL-7Rα variants in T1D disease pathogenesis are well-described, effects of γ c expression and availability for dependent receptors remain elusive. We investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(55 reference statements)
1
9
0
1
Order By: Relevance
“…Indeed, a previous study suggested that inactivation of FoxO1, a signaling mediator downstream of IGF1R whose activity is inhibited by IGF1 (29), upregulates expression of CD122 in naïve murine CD4 + T cells (64). There is a scarcity of literature on modulation of expression of CD132 levels on T cells (65,66), suggesting that IL-2 + IGF1 may constitute a novel means to sensitize naïve Tconv to cytokines whose receptors utilize the common γ-chain, including but not limited to IL-2 and IL-7 (10). These findings further promote the notion that the influence of IGF1 on the inflammatory/regulatory balance may be highly dependent on the cytokine milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a previous study suggested that inactivation of FoxO1, a signaling mediator downstream of IGF1R whose activity is inhibited by IGF1 (29), upregulates expression of CD122 in naïve murine CD4 + T cells (64). There is a scarcity of literature on modulation of expression of CD132 levels on T cells (65,66), suggesting that IL-2 + IGF1 may constitute a novel means to sensitize naïve Tconv to cytokines whose receptors utilize the common γ-chain, including but not limited to IL-2 and IL-7 (10). These findings further promote the notion that the influence of IGF1 on the inflammatory/regulatory balance may be highly dependent on the cytokine milieu.…”
Section: Discussionmentioning
confidence: 99%
“…These cells acquire effector function in the islets, a process dependent on cytokine action (34,35). Common g chain cytokines are important for T-cell proliferation and the generation of self-reactive T cells in autoimmune diseases (9). JAK inhibitors block the catalytic activity of JAKs and they are unlikely to affect cells that are not responding to cytokine stimulation, for example in a non-inflammatory setting (36).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations show that IL-2 and IL-21 are the prime cytokines needed for growth and differentiation of CTL (7,8). IL-7 and IL-15 are responsible for the generation of self-reactive T-cells in autoimmune diseases (9). Treatment with anti-IL-7 receptor-a reverses established autoimmune diabetes in NOD mice (10).…”
Section: Introductionmentioning
confidence: 99%
“…В модели воспаления in vitro при добавлении IL-7 увеличилась доля CD127 + CD132 + Tem, однако, влияния на экспрессию субъединиц IL-7R Tcm под действием провоспалительных факторов не было выявлено. Интересно, что по данным литературы, обнаруженное у пациентов с сахарным диабетом 1 типа увеличение экспрессии γ-цепи и IL-7Rα на CD4 + клетках памяти воздействовало на передачу сигналов от рецептора и продукцию цитокинов эффекторными Т-клетками [23]. Отсутствие контактов с АПК приводило к снижению содержания CD127 + CD132 + клеток в обеих субпопуляциях Т-клеток памяти, что может говорить о необходимости в дополнительном сигнале при стимуляции IL-7.…”
Section: Discussionunclassified